Lithium ferrite lithium supplement agent, positive electrode material, positive electrode plate and secondary battery
By covering the carbon material shell on the surface of lithium ferrate supplement and controlling related parameters, the problem of poor air stability is solved, high specific capacity and good capacity retention are achieved, which is suitable for improving the electrochemical performance of secondary batteries.
Patent Information
- Application Number
- CN202411982258.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
AI Technical Summary
The existing lithium ferrate supplements have poor air stability in the air, making it difficult for them to maintain capacity in the air for a long time to reach 80%.
The core-shell structure is formed to improve air stability by covering the shell layer of the carbon material on the surface of the core layer of the lithium ferrate supplement agent and controlling the ID/IG ratio, average thickness, radical concentration and mass fraction of the carbon element of the shell layer.
The excellent stability of lithium ferrate lithium supplement agent in the air is achieved. The specific capacity after 24 hours of exposure is higher than 570mAh/g, and the capacity retention rate is above 88%. It is suitable for long-term storage and improves the cycle stability of secondary batteries.
Smart Images

Figure CN119742350A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium ferrite supplement, a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] During the first charge of a lithium-ion battery, about 15% of the active lithium ions participate in the formation of a solid electrolyte interface (SEI) film, resulting in reversible lithium loss at the positive electrode, which in turn reduces the capacity of the battery. In order to solve the problem of lithium loss during the first charge of a lithium-ion battery, the industry usually adopts the method of adding a lithium supplement to the positive electrode material for pre-lithiation. So far, researchers have explored a variety of lithium supplements for positive electrode pre-lithiation, including Li2NiO2, Li2O2, Li2O2, Li2C4O4, Li2S, Li3N, Li6CoO4, and Li5FeO4 (LFO). However, the integration of binary compounds such as Li2O2, Li2O2, Li2C4O4, Li2S, and Li3N as lithium supplements into current battery production technology faces major challenges. The main problem is that they are incompatible with existing electrode preparation systems and are costly. In contrast, ternary compounds such as Li2NiO2, Li2C4O4, Li6CoO4, and LFO have better safety, stability, and compatibility.
[0003] Among them, LFO stands out for its rich raw material resources, high theoretical capacity (867mAh / g) and industrialization potential. However, LFO has extremely poor air stability. Once exposed to air, its specific capacity will drop rapidly. In order to solve the above technical problems, the researchers have improved the air stability of LFO to a certain extent by coating Li6CoO4 on the surface of LFO, doping zirconium in LFO, or coating the surface of LFO with polyethylene oxide-polypropylene oxide-polyethylene copolymer as a carbon coating. However, the capacity retention rate of LFO modified by the above method after exposure to air for 24 hours is difficult to reach 80%, and its long-term stability in air still needs to be improved. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a lithium ferrite lithium supplement, a positive electrode material, a positive electrode plate and a secondary battery, aiming to solve the technical problem of poor air stability of the existing lithium ferrite lithium supplement.
[0005] In a first aspect, an embodiment of the present application provides a lithium ferrite lithium supplement, the lithium ferrite lithium supplement comprises a core layer and a shell layer coated on the surface of the core layer, the material of the core layer comprises Li5FeO4, the material of the shell layer comprises a carbon material, and the lithium ferrite lithium supplement has an I D / I Gis 1.0-1.2, and the average thickness of the shell is 60nm-200nm.
[0006] In the technical solution of the embodiment of the present application, by forming a core-shell structure and controlling the average thickness of the shell layer, the shell layer can prevent the Li5FeO4 in the core layer from contacting with air to a certain extent. D / I G is the intensity ratio of the D peak and the G peak in the Raman spectrum, where the D peak is at 1350 cm -1 The peaks near the G peak are used to characterize defects. -1 The peak near is used to characterize the degree of graphitization, I D / I G The larger the value, the more defects there are. In this application, the lithium ferrite lithium supplement agent is D / I G Controlling it helps to form a suitable number of defects in the shell layer, promoting the adsorption of H2O and CO2 in the air by the shell layer, thereby improving the air stability of the lithium ferrite supplement.
[0007] In some embodiments, the free radical concentration of the lithium ferrite supplement is 1.2×10 13 spins / g~1.8×10 13 spins / g.
[0008] In the present application, by controlling the free radical concentration of the lithium ferrite lithium supplement agent within the above range, the obtained lithium ferrite lithium supplement agent has excellent air stability.
[0009] In some embodiments, the mass fraction of carbon in the lithium ferrite lithium supplement is 2% to 5%.
[0010] In this embodiment, by controlling the mass fraction of the carbon element, on the one hand, it helps to form a uniform and dense shell layer, further improving the air stability of the lithium ferrite lithium supplement, and on the other hand, it helps to improve the conductivity of the lithium ferrite lithium supplement and increase the lithium ion migration rate. After applying it to the positive electrode material, it can participate in the formation of the SEI film before the positive electrode active material during the first charge and discharge process, thereby improving the reversible capacity of the positive electrode material.
[0011] In some embodiments, the D50 particle size of the lithium ferrite lithium supplement is 3 μm to 6 μm.
[0012] In this embodiment, by controlling the D50 particle size of the lithium ferrite lithium supplement, on the one hand, the specific surface area of the lithium ferrite lithium supplement can be increased, so that the shell material forms a good bonding effect with H2O and CO2 in the air, and further reaction with the core material Li5FeO4 is inhibited; on the other hand, the lithium ferrite lithium supplement can be made easier to disperse and form a uniform positive electrode material with the positive electrode active material; on the other hand, its electron transfer rate and ion transfer rate can be increased, thereby improving the electrochemical performance of the formed positive electrode material.
[0013] In some embodiments, the specific capacity of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 24 hours is higher than 570 mAh / g; and / or, the specific capacity of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 48 hours is higher than 530 mAh / g; and / or, the specific capacity of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 72 hours is higher than 520 mAh / g.
[0014] In the present application, the lithium ferrite lithium supplement provided has excellent specific capacity and air stability. When the lithium ferrite lithium supplement is used to prepare positive electrode materials, it helps to improve the specific capacity of the prepared positive electrode materials, and then helps to improve the electrochemical performance of the secondary battery prepared using the positive electrode material, that is, it can improve the commercialization of the lithium ferrite lithium supplement in the application field of secondary batteries.
[0015] In some embodiments, the capacity retention rate of the lithium ferrite supplement after exposure to air at 25°C and 20% relative humidity for 24 hours is above 88%; and / or, the capacity retention rate of the lithium ferrite supplement after exposure to air at 25°C and 20% relative humidity for 48 hours is above 82%; and / or, the capacity retention rate of the lithium ferrite supplement after exposure to air at 25°C and 20% relative humidity for 72 hours is above 80%.
[0016] In the present application, the lithium ferrite lithium supplement provided has excellent air stability and is suitable for long-term storage, which is beneficial to improving the cycle stability of the secondary battery prepared using the lithium ferrite lithium supplement; at the same time, the capacity retention rate of the lithium ferrite lithium supplement after being exposed to the air for a period of time can still be maintained at a high level, which is beneficial to improving the electrochemical performance of the secondary battery prepared using the lithium ferrite lithium supplement.
[0017] In a second aspect, an embodiment of the present application provides a positive electrode material, which includes a positive electrode active material, a conductive agent, a binder and a lithium supplement agent, wherein the lithium supplement agent is the lithium ferrite lithium supplement agent of the first aspect of the present application.
[0018] In the technical solution of the embodiment of the present application, due to the use of the lithium ferrite lithium supplement agent in the above embodiment, the specific capacity of the prepared positive electrode material can be effectively improved.
[0019] In some embodiments, the mass ratio of the lithium supplement agent to the positive electrode active material is (1:100) to (5:100).
[0020] In this embodiment, if the amount of lithium supplement agent added is too little, the amount of lithium ions supplemented will be too little, and the lithium supplement effect of the lithium supplement agent will be poor; if the amount of lithium supplement agent added is too much, the electrochemical properties of the positive electrode material will be affected.
[0021] In some embodiments, the capacity retention rate of the cathode material described in the present application after 100 cycles at a rate of 0.33C is higher than 93%.
[0022] In this embodiment, the positive electrode material prepared using lithium ferrite lithium supplement has good cycle performance and high capacity retention rate, which is beneficial to improving the cycle stability of the secondary battery prepared using the positive electrode material and can extend the service life of the secondary battery, thereby helping to broaden the application range of the prepared secondary battery.
[0023] In a third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector and a positive electrode material located on one side or both sides of the current collector, and the positive electrode material is the positive electrode material of the second aspect of the present application.
[0024] In this embodiment, the positive electrode plate includes the above-mentioned positive electrode material, and thus has the performance of high capacity retention rate.
[0025] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet of the third aspect of the present application.
[0026] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high energy density and good cycle performance.
[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 TEM image of the lithium ferrite lithium supplement in Example 1;
[0030] Figure 2 The Raman spectra of the lithium ferrite supplement in Example 1 and Comparative Example 1 are shown;
[0031] Figure 3 The SEM images of the lithium ferrite supplement in Example 1 and Comparative Example 1 are shown;
[0032] Figure 4 The XRD spectra of the lithium ferrite supplement in Example 1 and Comparative Example 1 placed in air at 25° C. and 20% relative humidity for different time periods;
[0033] Figure 5 It is the GITT test diagram of the lithium ferrite lithium supplement in Example 1 and Comparative Example 1;
[0034] Figure 6 The data diagram of specific capacity of the lithium ferrite supplement in Example 1 and Comparative Example 1 when placed in air at 25° C. and 20% relative humidity for different time periods;
[0035] Figure 7 The specific capacity data of the lithium ferrite lithium supplement in Example 1 after being placed at 25° C. and different humidity conditions for different time periods;
[0036] Figure 8 The figure is a rate performance test diagram of the lithium ferrite lithium supplement in Example 1 and Comparative Example 1;
[0037] Fig. 9 The figure shows the rate performance and cycle performance test of the positive electrode sheet in the half-cell in Example 8 and Comparative Example 5;
[0038] Fig.10 The figure is a rate performance test diagram of the secondary battery in Example 9 and Comparative Example 6;
[0039] Fig.11 This is a test diagram of the cycle performance of the secondary battery in Example 9 and Comparative Example 6 at 0.5C. DETAILED DESCRIPTION
[0040] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0042] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0043] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0044] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0045] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0046] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0047] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0048] There is a problem of lithium loss during the first charge and discharge process of lithium-ion batteries. At present, it is generally used to add lithium supplements to the positive electrode materials for pre-lithiation to increase the capacity of the battery. LFO stands out among many lithium supplements due to its abundant raw material resources, high theoretical capacity (867mAh / g) and industrialization potential. Its charging and discharging voltage window is compatible with commercial positive electrode materials, and its production process is perfectly matched with the existing lithium-ion battery manufacturing process. Despite its many advantages, LFO's extremely poor air stability has hindered its commercialization progress. The carbon atoms in CO2 in the air can combine with the oxygen active sites on the LFO surface with an adsorption energy of -0.3963eV, and the oxygen atoms in CO2 can attach to the metal ion sites through Coulomb action with an adsorption energy of -0.5160eV. The above data show that CO2 is mainly adsorbed on the LFO surface through carbon atoms; when H2O in the air is adsorbed on the LFO surface, the hydrogen atoms in H2O form hydrogen bonds with the active oxygen on its surface with an adsorption energy of -0.2951eV, and the oxygen atoms in H2O are adsorbed on the metal ion sites through Coulomb action with an adsorption energy of -0.9155eV. The above data show that it is mainly the hydrogen atoms in H2O that form hydrogen bonds with the active oxygen on the LFO surface; from the above data, it can be seen that LFO has a strong adsorption effect on both H2O and CO2, and LFO is more likely to react with H2O in the air, resulting in instability when exposed.
[0049] In order to solve the technical problem of poor air stability of the above-mentioned LFO, in the first aspect, an embodiment of the present application provides a lithium ferrite lithium supplement, the lithium ferrite lithium supplement comprises a core layer and a shell layer coated on the surface of the core layer, the material of the core layer comprises Li5FeO4, the material of the shell layer comprises a carbon material, and the lithium ferrite lithium supplement has an I D / I G It is 1.0-1.2, specifically, it can be 1.0, 1.1, 1.2, etc., or it can be other values within this range, and is not specifically limited here. The average thickness of the shell is 60nm-200nm, specifically, it can be 60nm, 100nm, 200nm, etc., or it can be other values within this range, and is not specifically limited here.
[0050] In this application, ID / I G is the intensity ratio of the D peak and the G peak in the Raman spectrum, where the D peak is at 1350 cm -1 The peaks near the G peak are used to characterize defects. -1 The peak near is used to characterize the degree of graphitization, I D / I G The larger the value, the more defects there are. The present invention is to coat the surface of the Li5FeO4 core layer with a shell layer containing carbon material, and to D / I GBy controlling the thickness of the shell layer, the shell layer of the lithium ferrite supplement can form a good adsorption effect with H2O and CO2 in the air, preventing them from further reacting with Li5FeO4 in the core layer. In addition, by controlling the average thickness of the shell layer, it helps to further reduce the probability of H2O and CO2 in the air entering the core layer, thereby improving the air stability of the lithium ferrite supplement.
[0051] Furthermore, in some embodiments, the free radical concentration of the lithium ferrite supplement is 1.2×10 13 spins / g~1.8×10 13 spins / g, specifically, can be 1.2×10 13 spins / g, 1.4×10 13 spins / g, 1.8×10 13 spins / g, etc., may also be other values within this range and are not particularly limited here.
[0052] In the present application, by controlling the free radical concentration of the lithium ferrite lithium supplement, the air stability of the lithium ferrite lithium supplement is significantly improved.
[0053] Furthermore, in some embodiments, the mass fraction of carbon element in the lithium ferrite lithium supplement is 2% to 5%, specifically, it can be 2%, 3%, 4%, 5%, etc., or other values within the range, which is not particularly limited here.
[0054] In the present application, by controlling the mass fraction of carbon elements within the above range, it is helpful to form a uniform and dense shell layer, thereby effectively preventing the shell material from contacting with the air, and improving the air stability of the lithium ferrite lithium supplement. In addition, controlling the mass fraction of carbon elements within the above range helps to improve the conductivity of the lithium ferrite lithium supplement and increase the lithium ion migration rate. Furthermore, when the mass fraction of carbon elements is within the above range, the lithium ion migration rate is fast, which is beneficial to increase the reversible lithium capacity of the positive electrode material.
[0055] Furthermore, in some embodiments, the D50 particle size of the lithium ferrite lithium supplement is 3 μm to 6 μm, specifically, 3 μm, 4 μm, 5 μm, 6 μm, etc., or other values within the range, which are not particularly limited herein.
[0056] In the present application, the particle size of the lithium ferrite lithium supplement will have a certain influence on its dispersibility and effective specific surface area. Controlling the D50 particle size of the lithium ferrite lithium supplement within the above range can, on the one hand, improve its dispersibility, which is conducive to forming a uniform positive electrode material with the positive electrode active material; on the other hand, it helps to promote the adsorption of H2O and CO2 in the air by the shell material in the lithium ferrite lithium supplement, and further improve the air stability of the lithium ferrite lithium supplement; on the other hand, it is conducive to increasing the contact area between the lithium ferrite lithium supplement and the electrolyte, forming an SEI film, and increasing the migration rate of lithium ions in the positive electrode material, so that the prepared secondary battery has good electrochemical properties.
[0057] Further, in some embodiments, the specific capacity of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 24 hours is higher than 570 mAh / g; and / or, the specific capacity of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 48 hours is higher than 530 mAh / g; and / or, the specific capacity of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 72 hours is higher than 520 mAh / g.
[0058] In the present application, the lithium ferrite lithium supplement provided has excellent specific capacity and air stability. When the lithium ferrite lithium supplement is used to prepare positive electrode materials, it helps to improve the specific capacity of the prepared positive electrode materials, and then helps to improve the electrochemical performance of the secondary battery prepared using the positive electrode material, that is, it can improve the commercialization of the lithium ferrite lithium supplement in the application field of secondary batteries.
[0059] Further, in some embodiments, the capacity retention rate of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 24 hours is above 88%; and / or, the capacity retention rate of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 48 hours is above 82%; and / or, the capacity retention rate of the lithium ferrite lithium supplement after exposure to air at 25°C and 20% relative humidity for 72 hours is above 80%.
[0060] It should be noted that the preparation process of the electrode before the electrochemical performance test, including mixing, coating, slicing, etc., was carried out in air at 25°C and 20% relative humidity. The above capacity retention rates are all compared based on the performance of the newly prepared lithium ferrite lithium supplement electrode.
[0061] In the present application, the lithium ferrite lithium supplement provided has excellent air stability and is suitable for long-term storage, which is beneficial to improving the cycle stability of the secondary battery prepared using the lithium ferrite lithium supplement; at the same time, the capacity retention rate of the lithium ferrite lithium supplement after being exposed to the air for a period of time can still be maintained at a high level, which is beneficial to improving the electrochemical performance of the secondary battery prepared using the lithium ferrite lithium supplement.
[0062] Typically, but not limiting, the preparation method of the lithium ferrite supplement includes coating a carbon layer on the surface of Li5FeO4. Specifically, Li5FeO4 can be mixed with asphalt, and the calcination process can be optimized to prepare a lithium ferrite supplement having a carbon material shell layer coated on the surface of the Li5FeO4 core layer; wherein Li5FeO4 can be purchased or obtained by self-production. In particular, a two-stage calcination is adopted, first pre-calcined at 200℃~300℃ for 0.5~1.5h, and then calcined at 600℃~800℃ for 1~4h, preferably calcined at 600℃~800℃ for 1~3h, to obtain the lithium ferrite supplement. During the preparation process, the mass ratio of the lithium ferrite supplement to the asphalt is controlled to be (100:5)~(100:15), wherein the prepared lithium ferrite supplement has an I D / I G In the range of 1.0 to 1.2, the average thickness of the shell layer of the lithium ferrite lithium supplement is 60 nm to 200 nm. Therefore, the prepared lithium ferrite lithium supplement has excellent air stability.
[0063] In a second aspect, an embodiment of the present application provides a positive electrode material, which includes a positive electrode active material, a conductive agent, a binder and a lithium supplementer, wherein the lithium supplementer is the lithium ferrite supplementer of the first aspect of the present application, and the mass ratio of the lithium supplementer to the positive electrode active material is (1:100) to (5:100).
[0064] In this embodiment, by controlling the amount of the lithium supplement, on the one hand, it is beneficial for the lithium supplement to replace the positive electrode active material to participate in the formation of the SEI film, reduce the reversible lithium loss in the positive electrode active material, and improve the specific capacity of the positive electrode material. On the other hand, controlling the amount of the lithium supplement within the above range is beneficial to ensure the stability of the positive and negative electrode material structure during the cycle and improve the cycle life of the battery. Among them, if the amount of the lithium supplement added is too little, the number of supplemented lithium ions will be too small, and the lithium supplement effect of the lithium supplement is not good; and if the amount of the lithium supplement added is too much, it will affect the electrochemical properties of the positive electrode material.
[0065] Typically but not limiting, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel cobalt manganese oxide; the conductive agent includes at least one of carbon black, conductive carbon black, graphite, graphene, acetylene black, and Ketjen black; the binder includes at least one of polyvinyl alcohol, carboxymethyl cellulose, and polyacrylic acid.
[0066] Furthermore, in some embodiments, the capacity retention rate of the positive electrode material described in the present application after 100 cycles at a rate of 0.33C is higher than 93%.
[0067] In the present application, since the lithium ferrite supplement described in the first aspect of the present application is added to the positive electrode material, the cycle stability of the positive electrode material can be improved to a certain extent, which is beneficial to improving the cycle performance of the secondary battery and broadening the application field of the secondary battery.
[0068] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector and a positive electrode material located on one side or both sides of the current collector, wherein the positive electrode material is the positive electrode material of the second aspect of the present application.
[0069] Due to the use of the above positive electrode material, the positive electrode plate has good stability and electrochemical performance.
[0070] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate of the third aspect of the present application, and the secondary battery has excellent energy density and cycle stability.
[0071] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0072] 1. Preparation method
[0073]
Lithium ferrite lithium supplement
[0074] Example 1
[0075] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0076] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0077] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0078] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:8 to obtain a second mixture;
[0079] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 200° C., keeping the temperature for 1 hour, then raising the temperature to 700° C., keeping the temperature for 2 hours, to obtain a lithium ferrite lithium supplement.
[0080] Example 2
[0081] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0082] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0083] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0084] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:12 to obtain a second mixture;
[0085] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 300° C., keeping the temperature for 0.5 h, then raising the temperature to 800° C., keeping the temperature for 1 h, to obtain a lithium ferrite lithium supplement.
[0086] Example 3
[0087] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0088] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0089] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0090] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:12 to obtain a second mixture;
[0091] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 250° C., keeping the temperature for 1.5 hours, then raising the temperature to 600° C., keeping the temperature for 3 hours, to obtain a lithium ferrite lithium supplement.
[0092] Example 4
[0093] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0094] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0095] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0096] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:15 to obtain a second mixture;
[0097] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 200° C., keeping the temperature for 1 hour, then raising the temperature to 700° C., keeping the temperature for 2 hours, to obtain a lithium ferrite lithium supplement.
[0098] Example 5
[0099] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0100] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0101] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0102] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:5 to obtain a second mixture;
[0103] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 200° C., keeping the temperature for 1 hour, then raising the temperature to 700° C., keeping the temperature for 2 hours, to obtain a lithium ferrite lithium supplement.
[0104] Example 6
[0105] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0106] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0107] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0108] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:8 to obtain a second mixture;
[0109] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 200° C., keeping the temperature for 1 hour, then raising the temperature to 700° C., keeping the temperature for 4 hours, to obtain a lithium ferrite lithium supplement.
[0110] Example 7
[0111] An embodiment of the lithium ferrite lithium supplement agent of the present application, the preparation method of the lithium ferrite lithium supplement agent of the present embodiment is as follows:
[0112] S1, mixing nano-Fe2O3 and nano-Li2O in a molar ratio of 1:5 to obtain a first mixture;
[0113] S2, placing the first mixture in a tube furnace and sintering it at 700° C. in an argon atmosphere for 24 hours to obtain Li5FeO4;
[0114] S3, crushing Li5FeO4 to a particle size of 1 to 10 μm, and mixing the crushed Li5FeO4 with asphalt in a mass ratio of 100:8 to obtain a second mixture;
[0115] S4, adding the second mixture into a tubular furnace, calcining in an argon atmosphere, first raising the temperature to 200° C., keeping the temperature for 1 hour, then raising the temperature to 500° C., keeping the temperature for 4 hours, to obtain a lithium ferrite lithium supplement.
[0116] Comparative Example 1
[0117] A lithium ferrite lithium supplement agent, the preparation method of which is different from that of Example 1 only in that S3 and S4 are not included, and Li5FeO4 in S2 is crushed to a particle size of 1 to 10 μm to obtain the lithium ferrite lithium supplement agent.
[0118] Comparative Example 2
[0119] A lithium ferrite lithium supplement, the preparation method of which is different from that of Example 1 only in that, in S3, the mass ratio of Li5FeO4 to asphalt is 100:3.
[0120] Comparative Example 3
[0121] A lithium ferrite lithium supplement agent, the preparation method of which is different from that of Example 1 only in that, in S4, the second mixture is added into a tubular furnace and calcined in an argon atmosphere, the temperature is first raised to 200° C. and kept for 1 hour, then raised to 700° C. and kept for 5 hours to obtain the lithium ferrite lithium supplement agent.
[0122] Comparative Example 4
[0123] A lithium ferrite lithium supplement agent, the preparation method of which is different from that of Example 1 only in that, in S4, the second mixture is added into a tubular furnace, calcined under an argon atmosphere, the temperature is directly raised to 700° C., and kept warm for 2.5 hours to obtain the lithium ferrite lithium supplement agent.
[0124]
Cathode materials
[0125] Example 8
[0126] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material of this embodiment is as follows: NCM811, lithium ferrite lithium supplement, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 93.5:4:1:1.5 to prepare the positive electrode material, wherein the lithium ferrite lithium supplement is the lithium ferrite lithium supplement prepared in Example 1.
[0127] Afterwards, the positive electrode material was mixed with the solvent using N-methylpyrrolidone as solvent to prepare a positive electrode slurry, which was then coated on an aluminum foil. The coating amount of the positive electrode active material was 75 mg / cm 2 , and obtain the positive electrode.
[0128] Comparative Example 5
[0129] An embodiment of the positive electrode material of the present application, the preparation method of the positive electrode material of this embodiment is as follows: NCM811, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 97.5:1:1.5 to prepare the positive electrode material.
[0130] Afterwards, the positive electrode material was mixed with the solvent using N-methylpyrrolidone as solvent to prepare a positive electrode slurry, which was then coated on an aluminum foil. The coating amount of the positive electrode active material was 75 mg / cm 2 , and obtain the positive electrode.
[0131]
Secondary battery
[0132] Example 9
[0133] In one embodiment of the secondary battery of the present application, the positive electrode sheet prepared in Example 8 is combined with a SiO x The battery is composed of a composite negative electrode composed of and graphite (mass ratio is 1:8), wherein the electrolyte uses LiPF6 as the lithium salt with a concentration of 1 mol / L, and the solvent is a composite solvent of ethylene carbonate and dimethyl carbonate with a mass ratio of 3:7.
[0134] Comparative Example 6
[0135] In one embodiment of the secondary battery of the present application, the positive electrode sheet prepared in Comparative Example 5 is connected to the positive electrode sheet made of SiO x The battery is composed of a composite negative electrode composed of and graphite (mass ratio is 1:8), wherein the electrolyte uses LiPF6 as the lithium salt with a concentration of 1 mol / L, and the solvent is a composite solvent of ethylene carbonate and dimethyl carbonate with a mass ratio of 3:7.
[0136] 2. Test Method
[0137] 1. Property test of lithium ferrite lithium supplement
[0138] (1)I D / I G: Obtained by Raman spectroscopy (HORIBA XploRA Nano spectrometer), with an excitation wavelength of 633 nm;
[0139] (2) Average thickness of the shell: obtained by transmission electron microscopy (TEM, FEI-Talos F200S);
[0140] (3) Surface morphology: tested by scanning electron microscopy (SEM, TESCAN MIRALMS);
[0141] (4) Free radical concentration: tested by electron paramagnetic resonance (EPR, Bruker-EmxPlus);
[0142] (5) Mass fraction of carbon element: tested by infrared carbon and sulfur analyzer (HCS-140, Shanghai Dekai);
[0143] (6) D50 particle size: obtained by laser particle size analyzer;
[0144] (7) Air stability:
[0145] a) evaluating the air stability of the lithium ferrite supplement by comparing the changes in XRD peak intensity of the lithium ferrite supplement placed in air at 25°C and 20% relative humidity for different time periods;
[0146] b) evaluating the air stability of the lithium ferrite supplement by comparing the mass change of the lithium ferrite supplement when placed in air at 25°C and 20% relative humidity for different time periods: the test was conducted at 0.05°C;
[0147] c) Evaluate the air stability of the lithium ferrite supplement by comparing the capacity retention rate of the lithium ferrite supplement placed in air at 25°C and different relative humidity for different time periods: the test was conducted at 0.05°C;
[0148] (8) Electrochemical reaction kinetics: The galvanostatic intermittent titration technique (GITT) was used to test and calculate the ion diffusion coefficient D under the conditions of 3.65 V-3.75 V and 4.00-4.10 V;
[0149]
[0150] Where r is the particle size of the lithium ferrite supplement, τ is the pulse time, ΔEs is the total voltage change caused by the pulse, and ΔEt is the total transient voltage change of the battery within the time τ;
[0151] (9) Rate performance: The capacity is tested under 0.05C, 0.1C, 0.2C, 0.5C, and 1C conditions respectively.
[0152] 2. Property test of positive electrode
[0153] The capacity under 0.1C, 0.2C, 0.3C, 0.5C, 1C, and 2C conditions and the cycle performance under 0.33C conditions were tested respectively.
[0154] 3. Properties test of secondary batteries
[0155] The capacity of the secondary battery under 0.1C, 0.2C, 0.3C, 0.5C, 1C, and 2C conditions and the cycle performance under 0.5C condition were tested respectively.
[0156] III. Analysis of test results of various embodiments and comparative examples
[0157] Tables 1 to 3 show the performance test results of lithium ferrite lithium supplement.
[0158] Table 1
[0159]
[0160]
[0161] Table 2
[0162]
[0163] From the above test results, it can be seen that the air stability of the lithium ferrite supplement in Examples 1 to 7 is better than that in Comparative Examples 1 to 4, and the lithium ferrite supplement in the present application also has good stability in a high humidity environment, that is, the shell layer of the lithium ferrite supplement can effectively prevent H2O from contacting the LFO in the core layer. In addition, by comparing the performance test results of Examples 1 to 3 and Examples 4 to 5, it can be found that when the mass fraction of carbon element in the lithium ferrite supplement is 2% to 5%, its air stability is relatively better. The reason may be that within the above range, the shell layer has a better coating effect on the core layer, which is more conducive to preventing the LFO in the core layer from contacting with H2O and CO2 in the air; by comparing the performance test results of Examples 1 to 3 and Examples 6 to 7, it can be found that when the free radical concentration in the lithium ferrite supplement is 1.2×10 13 spins / g~1.8×10 13 spins / g, its air stability is better.
[0164] Table 3
[0165]
[0166] Furthermore, it can be seen from the data in Table 3 that the specific capacity of the lithium ferrite lithium supplement in the embodiment of the present application after being placed for 24 hours is higher than 570mAh / g, and the capacity retention rate is higher than 88%; the specific capacity after being placed for 48 hours is higher than 530mAh / g, and the capacity retention rate is higher than 82%; the specific capacity after being placed for 72 hours is higher than 520mAh / g, and the capacity retention rate is higher than 80%.
[0167] Further, Figure 1 This is a TEM image of the lithium ferrite lithium supplement in Example 1. It can be seen from the image that the lithium ferrite lithium supplement in the present application has a core-shell structure, the shell layer structure is uniform, and a good coating is formed on the core layer material.
[0168] Further, Figure 2 The Raman spectra of the lithium ferrite supplement in Example 1 and Comparative Example 1 are shown in FIG. 1 . As can be seen from the figure, the Raman spectra of Example 1 have a peak at 1350 cm -1 Nearby and 1580cm -1 Peaks D and G appear nearby, indicating that a shell layer containing carbon material is formed in the lithium ferrite lithium supplement of the present application.
[0169] Further, Figure 3 The SEM images of the lithium ferrite supplement in Example 1 and Comparative Example 1 show that the surface of the lithium ferrite supplement in the core-shell structure of the present application is smoother, while the surface of the lithium ferrite supplement without carbon coating is rougher. The accompanying drawings show that there is a dense shell layer on the surface of the lithium ferrite supplement of the present invention, which helps to improve the air stability of LFO.
[0170] Further, Figure 4 The XRD spectra of the lithium ferrite lithium supplement in Example 1 and Comparative Example 1 placed in air at 25°C and 20% relative humidity for different time periods. It can be seen from the figure that after being placed for 12 hours, the XRD peak intensity of the lithium ferrite lithium supplement in Example 1 has not changed significantly, indicating that it has good stability in the air; there is no obvious peak in the XRD spectrum of the lithium ferrite lithium supplement in Comparative Example 1 after being placed in the air for 12 hours, indicating that its air stability is poor.
[0171] Further, Figure 5 GITT test diagram of the lithium ferrite supplement in Example 1 and Comparative Example 1; it can be seen from the figure that LFO@C in Example 1 has a lower lithium ion extraction potential than LFO in Comparative Example 1 and can release more lithium ions. It is calculated that within the voltage range of 3.65V-3.75V, the diffusion coefficient D of the lithium ferrite supplement in Example 1 is 5.48×10 -11 cm 2 / s, the diffusion coefficient D of the lithium ferrite supplement in Comparative Example 1 is 4.96×10 -13 cm 2 / s, Example 1 is about 110 times that of Comparative Example 1. In the voltage range of 4.00V-4.10V, the diffusion coefficient D of the lithium ferrite supplement in Example 1 is 7.88×10 - 12 cm 2 / s, the diffusion coefficient D of the lithium ferrite supplement in Comparative Example 1 is 1.87×10 -12 cm 2 / s, and Example 1 is about 4 times that of Comparative Example 1. The above results are related to the formation of a large number of oxygen vacancy defects during the carbon coating process, which can effectively improve the migration path of lithium ions in LFO.
[0172] Further, Figure 6 The specific capacity data of the lithium ferrite lithium supplement in Example 1 and Comparative Example 1 placed in air at 25°C and 20% relative humidity for different time periods are shown. After 8 hours of placement, the specific capacity of the lithium ferrite lithium supplement in Example 1 is 796 mAh / g, and the capacity retention rate is 99.1%. After 24 hours of placement, the specific capacity is 790.1 mAh / g, and the capacity retention rate can reach 98.4%. After 48 hours of placement, the specific capacity is 764 mAh / g, and the capacity retention rate can reach 95.2%. After 72 hours of placement, the specific capacity is 745 mAh / g, and the capacity retention rate can reach 92.8%. The capacity retention rate of the lithium ferrite lithium supplement in Comparative Example 1 is reduced to 0. This result also shows that the lithium ferrite lithium supplement in the examples of the present application has excellent air stability.
[0173] Further, Figure 7 The specific capacity data of the lithium ferrite lithium supplement in Example 1 after being placed at 25°C and different humidity conditions for different time periods. It can be seen from the figure that after being placed in air with a relative humidity of 35% for 24 hours, the specific capacity of the lithium ferrite lithium supplement in Example 1 is 779 mAh / g, and the capacity retention rate is 97.1%; in addition, after being placed under a relative humidity of 50% for 8 hours, the specific capacity of the lithium ferrite lithium supplement is still maintained at above 754 mAh / g, and the capacity retention rate is 94%. This result also shows that the shell layer in the lithium ferrite lithium supplement described in the present application can effectively prevent H2O in the air from reacting with LFO in the core layer, thereby improving its air stability.
[0174] Further, Figure 8 It is a rate performance test diagram of the lithium ferrite lithium supplement in Example 1 and Comparative Example 1. It can be seen from the figure that when the current density increases from 0.05C to 1C, the capacity retention rate of the lithium ferrite lithium supplement in Example 1 is 88%; in contrast, the lithium ferrite lithium supplement in Comparative Example 1 undergoes significant capacity decay under the same conditions, and its capacity retention rate is nearly 43%. This result shows that after carbon coating, the electrochemical performance of the lithium ferrite lithium supplement of the present application is also significantly improved.
[0175] Further, Fig. 9 The figure is a test diagram of the rate performance and cycle performance of the positive electrode plates in the half-cell in Example 8 and Comparative Example 5. It can be seen from the figure that the specific capacity of the positive electrode material in Example 8 does not drop suddenly at the rates of 0.1C, 0.2C, 0.3C, 0.5C, 1C, and 2C, and the capacity retention rate after 100 cycles at 0.33C is higher than 93%. This result shows that by adding lithium ferrite lithium supplement, the rate performance and cycle performance of the positive electrode plate are improved to a certain extent.
[0176] Further, Fig.10 The figure is a rate performance test diagram of the secondary battery in Example 9 and Comparative Example 6. It can be seen from the figure that the secondary battery described in the present application has good rate performance, and its specific capacity is significantly increased compared with the secondary battery without adding lithium ferrite lithium supplement.
[0177] Further, Fig.11 The test graph of the cycle performance of the secondary battery at 0.5C in Example 9 and Comparative Example 6 shows that the cycle performance of Example 9 is better than that of Comparative Example 6, and its specific capacity is higher. This result shows that the present application significantly improves the energy density and cycle performance of the secondary battery by adding lithium ferrite lithium supplement.
[0178] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium ferrite lithium supplement, characterized in that: The lithium ferrite lithium supplement comprises a core layer and a shell layer coated on the surface of the core layer, the material of the core layer comprises Li5FeO4, the material of the shell layer comprises a carbon material, and the lithium ferrite lithium supplement comprises a core layer and a shell layer coated on the surface of the core layer. D / I G is 1.0-1.2, and the average thickness of the shell layer is 60nm-200nm.
2. The lithium ferrite supplement according to claim 1, characterized in that: The free radical concentration of the lithium ferrite supplement is 1.2×10 13 spins / g~1.8×10 13 spins / g.
3. The lithium ferrite supplement according to claim 1, characterized in that: The mass fraction of carbon element in the lithium ferrite lithium supplement is 2% to 5%.
4. The lithium ferrite supplement according to any one of claims 1 to 3, characterized in that: The D50 particle size of the lithium ferrite lithium supplement is 3 μm to 6 μm.
5. The lithium ferrite supplement according to any one of claims 1 to 3, characterized in that: Includes at least one of the following features: (1) The specific capacity of the lithium ferrite supplement after exposure to air at 25° C. and 20% relative humidity for 24 hours is higher than 570 mAh / g; (2) The specific capacity of the lithium ferrite supplement after exposure to air at 25° C. and 20% relative humidity for 48 hours is higher than 530 mAh / g; (3) The specific capacity of the lithium ferrite supplement after exposure to air at 25° C. and 20% relative humidity for 72 hours is higher than 520 mAh / g.
6. The lithium ferrite supplement according to any one of claims 1 to 3, characterized in that: Includes at least one of the following features: (1) The capacity retention rate of the lithium ferrite supplement after exposure to air at 25° C. and 20% relative humidity for 24 hours is above 88%; (2) The capacity retention rate of the lithium ferrite supplement after exposure to air at 25° C. and 20% relative humidity for 48 hours is above 82%; (3) The capacity retention rate of the lithium ferrite supplement after being exposed to air at 25° C. and 20% relative humidity for 72 hours is above 80%.
7. A positive electrode material, characterized in that: The positive electrode material includes a positive electrode active material, a conductive agent, a binder and a lithium supplement, wherein the lithium supplement is the lithium ferrite lithium supplement as described in any one of claims 1 to 6; the mass ratio of the lithium supplement to the positive electrode active material is (1:100) to (5:100).
8. The positive electrode material according to claim 7, characterized in that The capacity retention rate of the positive electrode material after 100 cycles at a 0.33C rate is higher than 93%.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode material located on one side or both sides of the current collector; wherein the positive electrode material is the positive electrode material according to claim 8.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet as claimed in claim 9.